A new treatment for congenital nystagmus. Issue 1 (January 1980) - Abadi, R V; Carden, D; Simpson, J
Abstract : Congenital nystagmus is a disorder of eye movement with an associated reduction in visual acuity. The latter is mainly due to the intensity of the nystagmus (amplitude times frequency) allowing the object of regard to spend only a short time on the fovea. Training patients by an auditory feedback technique to control the nystagmus enables visual sensitivity to improve. This method is compared with present alternatives, and further studies are suggested.